Pengaruh Konsentrasi Ion Aktif Erbium (Er3+) pada Sifat Fisis Medium Gelas Borat-Lithium - Rajagukguk, Juniastel; Fitrilawati, Fitrilawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2018)
Lithium-Borate glasses medium doped Erbium (Er3+) active ion have been prepared by melting-quenching technique. The glasses medium followed composition (mol%): 65 â€“ x)B2O3 - 5ZnO - 5Li2O - 15 Na2O - 10PbO - xEr2O3 (with Â x = 0; 0,05; 0,1; 0,5; 1,0; 2,0 dan 4,0 mol%). Sample with powder form are mixed in the crucible alumina and melted at temperature 1200 oC by using of electrical furnance. After poured in to stainless stell, Â glasses sample were annealed with the decreases rate 7oC per minute. Physical properties og glass medium such as density, molar volume and refractive index were inviestigated. From measured results can be known that Er3+ ion doped with lithium borate glass can affect physical properties of glass host medium. Density of glass is increased from 2.96 gr/cm3 (x = 0.1 mol%) to 3.185 gr/cm3 (x = 4 mol%). Refractive index of glass medium also increased with addition Er3+ ion concentration. The maximum refractive index is obtained when Er3+ ion concentration of 2.0 mol%. Based on research results can be explained that Er3+ doped Lithium-Borat glasses can be used as one of optical gain candidate.